New paradigms in cervical cancer prevention: opportunities and risks - Giorgi Rossi Paolo; Ronco Guglielmo (BMC, 2008)
Testing for the DNA of high-risk types of papilloma virus (HPV) is more sensitive than cytology in detecting pre-cancerous lesions. One of the main advantages will be the possibility of applying prolonged screening intervals. However adequate screening protocols (age of start and stop, screening intervals, management of HPV positive women) need to be applied in order to avoid over-referral to colposcopy and over-treatment and to maintain sustainable costs. Further follow-up of running trials and research on molecular markers will better define these parameters. The new situation will require organised screening programmes with rigorous protocols and monitoring. This will be even more needed when women vaccinated for HPV 16 and 18 will be screened. Research on how to best screen vaccinated women is a priority. This paper proposes an overview of the plausible impact of new technologies in cervical cancer screening in the near future and in the vaccinated cohorts.